Dynamics of Polyamines, Proline, and Ethylene Metabolism under Increasing Cold in Winter Oilseed Rape - Jankovska-Bortkevič, Elžbieta; Jurkonienė, Sigita; Gavelienė, Virgilija; Šveikauskas, Vaidevutis; Mockevičiūtė, Rima; Vaseva, Irina; Todorova, Dessislava; Žižytė-Eidetienė, Marija; Šneideris, Donatas; Prakas, Petras (International journal of molecular sciences, 2023)
Cold stress is among the most important environmental factors reducing the yield of crops. The present study aimed to investigate the impact of increasing cold stress conditions on winter oilseed rape polyamines, proline, and ethylene metabolism in acclimated and non-acclimated winter oilseed rape. This study was carried out under controlled conditions in the laboratory. The winter oilseed rape hybrid ‘Visby’ was used in the experiment. Acclimated and non-acclimated plants were subjected to a two-day-long increasing cold (from −1 °C to −3 °C) treatment. HPTLC, RT-qPCR, spectral analysis, and gas chromatography methods were used to analyse the levels of polyamines, gene expression, proline, and ethylene, respectively. This study showed a decrease in putrescine, spermidine, and spermine content during cold acclimation and a decrease in putrescine and spermidine levels at sub-zero temperatures. There were intensive changes in ADC2 gene expression, proline, and ethylene levels in non-acclimated plants: a substantial increase after exposure to −1 °C temperature and a sharp decrease after exposure to −3 °C temperature. The changes in these parameters were lower or absent in acclimated plants. The phenomena observed in this study add new insights to the knowledge about the plant stress response and suggest questions to be answered in the future.